First Report of White Thread Blight Caused by Ceratobasidium niltonsouzanum on Yerba Mate in Argentina - Bernanrdi Lima, Nelson (2019)
Yerba mate (Ilex paraguariensis A.St.-Hil.) is a native species of the subtropical and temperate regions of South America. In the Misiones province, in northeastern Argentina, yerba mate is an important agricultural crop grown on approximately 150,000 ha. In March 2019, diseased leaves and stems from four fields near Comandante Andresito city were received for diagnosis at the Instituto de Patología Vegetal (IPAVE) and Instituto Nacional de Tecnología Agropecuaria, Argentina.